Artificial Synapses Emulated by an Electrolyte‐Gated Tungsten‐Oxide Transistor. Issue 34 (4th July 2018) - Yang, Jing‐Ting; Ge, Chen; Du, Jian‐Yu; Huang, He‐Yi; He, Meng; Wang, Can; Lu, Hui‐Bin; Yang, Guo‐Zhen; Jin, Kui‐Juan
Abstract: Considering that the human brain uses ≈10 15 synapses to operate, the development of effective artificial synapses is essential to build brain‐inspired computing systems. In biological synapses, the voltage‐gated ion channels are very important for regulating the action‐potential firing. Here, an electrolyte‐gated transistor using WO3 with a unique tunnel structure, which can emulate the ionic modulation process of biological synapses, is proposed. The transistor successfully realizes synaptic functions of both short‐term and long‐term plasticity. Short‐term plasticity is mimicked with the help of electrolyte ion dynamics under low electrical bias, whereas the long‐term plasticity is realized using proton insertion in WO3 under high electrical bias. This is a new working approach to control the transition from short‐term memory to long‐term memory using different gate voltage amplitude for artificial synapses. Other essential synaptic behaviors, such as paired pulse facilitation, the depression and potentiation of synaptic weight, as well as spike‐timing‐dependent plasticity are also implemented in this artificial synapse. These results provide a new recipe for designing synaptic electrolyte‐gated transistors through the electrostatic and electrochemical effects. Abstract : An electrolyte‐gated transistor using WO3 with a unique tunnel structure to successfully emulate the synaptic functions of both short‐term and long‐term plasticity is proposed. Short‐term plasticity is mimicked with the help of electrolyte ion dynamics under low gate bias, and the long‐term plasticity is realized via proton insertion in WO3 under high gate bias.